Organizacija informacijskog sistema za automatsko projektiranje : magistarski rad - Milošević, Veljko (Elektrotehnički fakultet, 1982)
SUMMARY: The computer aided design becomes a necessity of modern manufacturing. Information storage and retrieval system ia an indivisable part of every CAD system, so that their organization analysis present their essential part. Since the computer aided design can be widely applied in the field of design, some characteristics of a certain number of CAD systems are presented in this work. The emphasis is being put on the use of the computers in the preparation of the input data for NC machines. The characteristics of the information storage and retrieval system in CAD and their main characteristic, i. e. level of dialogue between the designer and the CAD system, are pointed out. The organization of the system for the CAD is illustrated by the example of the first Yugoslav system SAPOR-S for the automatic design of technological process and input data for NC lathes.